Relationship between Academic Self-Efficacy and Academic Procrastination: Understanding How Academic Self Efficacy affect Academic Procrastination in Undergraduate Students - Zarmeen Qureshi (Journal of Applied Research and Multidisciplinary Studies, 2023)
Academic Procrastination is seen as one of the hurdles for the student's success. This is increasing more now and affecting their grades and also, mental health. Although many factors affect procrastination, one of them is academic self-efficacy itself. This research was conducted to find the extent to which academic self-efficacy affects academic procrastination in undergraduate students. We conducted our research on 330 undergraduate students from Beaconhouse National University in Lahore Pakistan. We gave them an online questionnaire to fill which took not more than one minute. For collecting and analyzing the data we selected two scales: Procrastination Assessment Scale for Students and Academic Self-Efficacy and Efficacy for Self-Regulated Learning scale. And we have made a conclusion that Student Academic procrastination is influenced by academic self-efficacy, based on our detailed correlation and regression research. They have an inverse relationship. Their link is statistically significant. Moreover, it was also discovered that students who recognize that procrastination is a problem and not the same ratio are willing enough to decrease it